The Drosophila fragile X mental retardation protein controls actin dynamics by directly regulating profilin in the brain. - Reeve, S.P.; Bassetto, L.; Genova, G.K.; Kleyner, Y.; Leyssen, M.; Jackson, F.R.; Hassan, B.A. (Current Biology, 2005)
Loss of Fragile X mental retardation protein (FMRP) function causes the highly prevalent Fragile X syndrome [1 and 2]. Identifying targets for the RNA binding FMRP is a major challenge and an important goal of research into the pathology of the disease. Perturbations in neuronal development and circadian behavior are seen in Drosophila dfmr1 mutants. Here we show that regulation of the actin cytoskeleton is under dFMRP control. dFMRP binds the mRNA of the Drosophila profilin homolog and negatively regulates Profilin protein expression. An increase in Profilin mimics the phenotype of dfmr1 mutants. Conversely, decreasing Profilin levels suppresses dfmr1 phenotypes. These data place a new emphasis on actin misregulation as a major problem in fmr1 mutant neurons.